Complete Response II – Sinusoidal Input

If the input voltage to the RC circuit considered previously is sinusoidal $v(t)=V_s \cos(\omega t+\psi)$, then the DE becomes

$\displaystyle v_R(t)+v_C(t)=\tau\frac{d}{dt} v_c(t)+v_c(t)
=\tau\dot{v}_c(t)+v_c(t)=V_s \cos(\omega t+\psi)$ (146)

The homogeneous solution is the same as before $v_h(t)=A e^{-t/\tau}$. To find the particular solution $v_p(t)$ as the steady state response to the input $V_s\cos(\omega t+\psi)$, we first assume the input is $V_s e^{j(\omega t+\psi)}$, and the particular solution is $y_p(t)=B e^{j\omega t}$ and $\dot{y}_p(t)=j\omega B e^{j\omega t}$. The DE can now be written as

$\displaystyle \tau\dot{v}_c(t)+v_c(t)=j\omega\tau Be^{j\omega t}+Be^{j\omega t}
=(j\omega\tau +1) B e^{j\omega t} =V_s e^{j\omega t} e^{j\psi}$ (147)

Solving for $B$ we get

$\displaystyle B=\frac{V_s e^{j\psi}}{j\omega\tau+1}$ (148)

Substituting $B$ back into $y_p(t)$ we get

$\displaystyle y_p(t)=B e^{j\omega t}=\frac{V_s e^{j\psi}}{j\omega\tau+1} e^{j\omega t}
=\frac{V_s}{\sqrt{(\omega\tau)^2+1}}e^{j(\omega t+\psi-\phi)}$ (149)

where $\phi=\tan^{-1}\omega\tau$. Taking the real part of the above we get the particular solution as the response to the actual input $V_s\cos(\omega t+\psi)=Re(V_s e^{j(\omega t+\psi)})$

$\displaystyle y_p(t)=Re\left[\frac{V_s e^{j(\omega t+\psi-\phi)}}{j\omega\tau+1}\right]
=\frac{V_s}{\sqrt{(\omega\tau)^2+1}}\cos((\omega t+\psi-\phi)$ (150)

Alternatively, we can also use the phasor method. The input can be written as

$\displaystyle v(t)=V_s \cos(\omega t)=Re[\dot{V} e^{j\omega t}]$ (151)

where $\dot{V}=V_s\; e^{j\psi}$ is the phasor form of the input voltage. The voltage across $C$ is (voltage divider):
$\displaystyle \dot{V}_C$ $\displaystyle =$ $\displaystyle \dot{V} H(\omega)=\dot{V} \frac{Z_C}{Z_R+Z_C}
=\dot{V} \frac{1/j\...
...c{\dot{V}}{j\omega \tau+1}
=\frac{\dot{V}}{\sqrt{(\omega \tau)^2+1}\;e^{j\phi}}$  
  $\displaystyle =$ $\displaystyle \frac{\dot{V}\;e^{-j\phi}}{\sqrt{(\omega \tau)^2+1}}
=\frac{V_se^...
...\sqrt{(\omega \tau)^2+1}}
=\frac{V_se^{j(\psi-\phi)}}{\sqrt{(\omega \tau)^2+1}}$ (152)

where $\phi=\tan^{-1}\omega\tau$, and $H(\omega)$ is the frequency response function (FRF) of the system:

$\displaystyle H(\omega)=\frac{Z_C}{Z_C+Z_R}=\frac{1/j\omega C}{R+1/j\omega C}
=\frac{1}{\sqrt{1+(\omega\tau)^2}} e^{-j\phi}$ (153)

In time domain the steady state voltage $v_p(t)$ is:
$\displaystyle v_p(t)$ $\displaystyle =$ $\displaystyle Re\left[\dot{V}_C e^{j\omega t} \right]
=Re\left[ \frac{V_s e^{j(...
...)^2+1}} \right]
= \frac{V_s}{\sqrt{(\omega \tau)^2+1}} \cos(\omega t+\psi-\phi)$  
  $\displaystyle =$ $\displaystyle \vert H(\omega)\vert V_s\cos(\omega t+\psi-\angle H(\omega))$ (154)

Note that this steady state output is simply the input $v(t)=V_S\cos(\omega t+\psi)$ scaled by the magnitude of the FRF $\vert H(\omega)\vert=1/\sqrt{(\omega\tau)^2+1}$ with a phase shift equal to the phase of the FRF $\angle H(\omega)=-\phi$.

We get the complete solution as the sum of the homogeneous and particular solutions:

$\displaystyle v_C(t)=v_h(t)+v_p(t)=
\frac{V_s}{\sqrt{(\omega \tau)^2+1}}\cos(\omega t+\psi-\phi)+A e^{-t/\tau}$ (155)

From the initial condition $v_C(0)=V_0$, we have

$\displaystyle v_C(t)\bigg\vert _{t=0}=v_C(0)
=V_0=\frac{V_s}{\sqrt{(\omega \tau)^2+1}}\cos(\psi-\phi)+A$ (156)

Solving for $A$ we get

$\displaystyle A=V_0-\frac{V_s}{\sqrt{(\omega \tau)^2+1}}\cos(\psi-\phi)$ (157)

Substituting $A$ back to the expression of $v_C(t)$, we get

$\displaystyle v_C(t)=\frac{V_s}{\sqrt{(\omega \tau)^2+1}}\cos(\omega t+\psi-\ph...
...left[V_0-\frac{V_s}{\sqrt{(\omega \tau)^2+1}}\cos(\psi-\phi)\right] e^{-t/\tau}$ (158)

The same result can also be obtained using the Laplace transform method.

Again we consider a short-cut method, by generalizing the result above to

$\displaystyle f(t)=f_{\infty}(t)+[f(0)-f_{\infty}(0)]e^{-t/\tau}$ (159)

in terms of three essential components
  1. $f(0)$: the initial value (same as before);
  2. $f_{\infty}(t)$: the steady state response, and $f_{\infty}(0)=f_{\infty}(t)\big\vert _{t=0}$ is $f_{\infty}(t)$ evaluated at $t=0$;
  3. $\tau$: the time constant of the system (same as before).
Note that when the input $V_s$ is a constant, the steady state response $f(\infty)$ is a constant, but when the input $V_s\cos(\omega t+\psi)$ is sinusoidal, the steady state response $f_{\infty}(t)$ is a function of time $t$, but its evaluation at $t=0$ $f_{\infty}(0)=f_{\infty}(t)\big\vert _{t=0}$ is still a constant. We see that the complete response is composed of the steady state response and the exponential decay of the difference between the initial value $f(0)$ and the steady state response evaluated at $t=0$.

If the initial voltage on $C$ is zero $V_0=0$, then

$\displaystyle v_C(t)=\frac{V_s}{\sqrt{(\omega \tau)^2+1}}[\cos(\omega t+\psi-\phi)
-\cos(\psi-\phi) e^{-t/\tau}]$ (160)

Note that the initial magnitude of the transient component at $t=0^+$ varies depending on the angle $\psi-\phi$.

The three cases for $\psi-\phi$ to be $0^\circ$, $90^\circ$, and $180^\circ$ are shown below:

first_order_response.gif first_order_response_0.gif first_order_response_90.gif first_order_response_180.gif

Example 2:

An electromagnet, modeled by a resistor $R=20\Omega$ and $L=0.3H$, is powered by sinusoidal voltage of $120V$ and $60Hz$. Find the current through the circuit when the switch is closed at $t=0$ when the phase angle happens to be $\psi=10^\circ$, i.e., $v(t)=120\sqrt{2}\;
\cos(6.28\times 60 t+10^\circ)$.

electromagnet1.gif